Terrestrial Signature of a Recently-Tidewater Glacier and Adjacent Periglaciation, Windy Glacier (South Shetland Islands, Antarctic) - Kreczmer, Kacper; Dąbski, Maciej; Zmarz, Anna (Frontiers in Earth Science, 2021)
Contemporary retreat of glaciers, well visible in the West Antarctic region. The aim of this study is to identify, map and quantify terrestrial glacial and periglacial landforms developed in front of Windy Glacier (Warszawa Icefield, King George Island, South Shetlands), which recently turned from being tidewater to land-terminating, and on near-by Red Hill. The study is based on an orthophoto map and a DEM elaborated with a use of images obtained during a UAV BVLOS photogrammetric survey in 2016, Google Earth Pro images from 2006 and an orthophoto map from 1978/1979. The geomorphological map obtained includes 31 types of landforms and water bodies, grouped into: (1) glacial depositional landforms, (2) fluvial and fluvioglacial landforms, (3) littoral and lacustrine landforms, (4) solifluction landforms, (5) scarps and taluses, (6) patterned ground, (7) debris flows, landslides and mudflows, (8) water bodies, (9) other (bedrock, boulders, glacial ice, snow patches, not recognized surface). Most area is occupied by glacial lagoon, fluvial and fluvioglacial landforms, not recognized surfaces and littoral landforms. Between 2006 and 2016 the glacier deposited a well-developed patch of fluted moraine with small drumlins. We recognize the glacial-periglacial transition zone between 41 m and 47 m GPS height. above which solifluction landforms and sorted patterned ground dominate. Advantages of UAV and BVLOS missions are highlighted and problems with vectorization of landforms are discussed. Distinction between flutes and small drumlins is shown on length-to-elongation and length-to-width diagrams and critical reference to previous geomorphological mappings on King George Island is presented.